CHBR: Contact History Based Routing in Time Varying Approach - S Patel, Pravesh; Shah, Hemal; Kosta, Yogeshwar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In Delay tolerant network having intermittent connectivity so there is no guarantee of finding a complete communication path that connecting the source and destination. There no any end to end connectivity for delay-tolerant network selection of routing protocol is important to deliver the message in an efficient way and increases chance to deliver a message to the destination. Some existing routing protocols improve the delivery ratio but it also increases the overhead. Our paper proposed Contact History Based Routing (CHBR) that use Neighborhood Index and Time varying properties such as temporal distance, Temporal Diameter and centrality for benchmarking the existing routing protocol. First, temporal metrics are evaluated for synthetic and real trace data. Then CHBR protocol is compared with the Epidemic and PROPHET for delivery ratio, overhead and the number of messages dropped. This has been carried using Opportunistic Network Environment simulator under real and synthetic datasets.